Living with air-conditioning: experiences in Dubai, Chongqing and London. Issue 1 (9th February 2022) - Murtagh, Niamh; Badi, Sulafa; Shi, Yaling; Wei, Shen; Yu, Wei
Extreme heat is a likely consequence of global warming, leading to increased mortality and reduced wellbeing. There is limited research evidence of experiences of living with and without air-conditioning (AC), commonly regarded as the sole technological solution, but such knowledge is essential to progressing alternative approaches. A total of 72 participants were interviewed in an exploratory cross-cultural phenomenological study in Dubai (United Arab Emirates—UAE), Chongqing (China) and London (UK). In Dubai and Chongqing, AC was ubiquitous and central to life in the hotter months, although not for all socio-economic groups. AC enabled indoor work to proceed, but a restricted indoor life meant less exercise, less social interaction and health issues. Participants had over-adapted, not to heat but to cold indoor temperatures, which were uncomfortable for many. In London, AC was not yet used, but the purchase of AC was being contemplated. The London participants showed a range of behavioural adaptations to heat. To reduce dependence on AC, regulations and behaviour change interventions regarding AC settings should focus on acclimatisation to heat. Changes in societal patterns, such as workhours, and behavioural adaptations, such as informed use of shading, can help mitigate heat. Deconstruction of the meanings of AC-related thermal comfort is needed to incorporate physiological, behavioural and social responses. Policy relevance: The study findings show the following: AC technology is already culturally embedded in societies in hot climates, but is not yet seen as a necessity in temperate climates, offering a window of opportunity. This window could close rapidly, so initiatives are needed now to encourage householders to improve heat protection around their homes. In hot climates, while AC enables life to continue, it is not a panacea. AC does not provide thermal comfort universally: people do not experience AC as providing a comfortable environment. Better regulation of building and urban design is needed to ensure climate and context appropriateness. Behaviour change interventions to reduce the overuse of AC are recommended to focus on health as well as energy. Existing discourses on AC as the unique and adequate solution to future heat must be challenged in order to open up the discussion to include behavioural, social, built environment and other technological solutions.